(untitled) (Research, Society and Development, 2017)
The eighteenth century in Portugal is marked by the development of an intellectual thought that tried to modernize not only anthe administrative machine, but the education and the knowledge production in the Metropolis and in its Colonies. The present work aims to contribute to the history of knowledge, more specifically, the contribution of the Portuguese Enlightenmentists to the educational assumptions as a conditioning element of the civilization process and the problems arising from the teachers’ acting to the construction of this political and educational project of knowledge in the Northern Captaincies.Theoretically we will be guided by Norbert Elias when we think education as a conditioning in which men have become civilized in a historical process of teaching and learning that also became essential to the so-called development of manners and behaviors and directly responsible for the formation of a model of civilization and knowledge.As a methodological proposal we will be close to the perspective of the Social History of Knowledge of Peter Burke, because when we study the authors mentioned above, besides the Statute of the University of Coimbra and the Manuscripts of the Ultramarine Historical Archive we will analyze the practice, the reception and the behavior of the educational presuppositions of the Portuguese Enlightenment in the Captaincies of Pernambuco and annexes.From the documentary analysis we find that the educational presuppositions of the Portuguese Enlightenment had difficulties to be implanted in the colony, with that achieved few results in the Civilizing Process.